Cal State East Bay Magazine, for university alumni and friends - CSUEB Alumni Association::::::; CSUEB Office of University Advancement::::::; CSUEB Office of University Communications:::::: (2012)
The successor to Haywire, Cal State East Bay Magazine was published two or three times a year by the CSUEB Alumni Association and the CSUEB Office of University Advancement's Communications Department for alumni and friends of California State University, East Bay.